Culturally appropriate terminologies in health research: a participatory study with pregnant and breastfeeding mothers in Uganda - Nakijoba, Ritah; Twimukye, Adelline; Bayigga, Josephine; Kawuma, Aida N.; Asiimwe, Simon Peter; Byenume, Fredrick; Kyeyune, Jacqueline; Nabukenya, Sylvia; Ojara, Francis Williams; Waitt, Catriona (Frontiers in Communication, 2025)
BackgroundThe language used in research and health programs is crucial in influencing participation and ensuring the acceptability of programs and the adoption of research outcomes. The use of alienating language may present a barrier for research participants hence the need to identify accurate, respectful, relevant, and acceptable terms for respective study populations. The study explored commonly used terminologies during research involving pregnant and lactating mothers using public engagement and participatory approaches in Uganda.MethodsA cross-sectional qualitative study was conducted in August 2023 among 5 ethnically diverse communities with different languages and from different regions across Uganda. Data were collected through 18 focus group discussions (FGDs) comprising community members and one comprising the community advisory board (CAB) using a participatory approach. An interview guide exploring perceptions and experiences on research, common and preferred terms for specific terminologies used among pregnant and lactating mothers as well as disliked words guided the discussion. Transcription was done verbatim in English. Nvivo version 14 software was used to organize and manage the data appropriately based on themes and subthemes.ResultsA consensus on the preferred terminologies to communicate about our research studies involving pregnant and lactating mothers was reached. The study revealed that words used in research that did not specify sex were described as disrespectful, inappropriate or confusing. Language defining a person on the basis of anatomical or physiological characteristics was considered ‘embarrassing’ and labelling individuals based on their conditions was construed as stigmatising. Participants recommended that researchers be mindful of any terms that could be perceived as embarrassing or inappropriate within the community, ensure clear communication of research terms to participants, and train healthcare workers on the use of appropriate health language. The importance of providing feedback regarding study findings was emphasised.ConclusionThe findings highlight the importance of using culturally sensitive language in health research to improve engagement and participation. By adopting community-preferred terms, researchers can avoid confusion and stigma fostering respectful health communication. The findings offer guidance for future research, advocating for community-driven inclusive language in research involving pregnant and breastfeeding women. For healthcare workers, training in empathetic communication and cultural competence is crucial to improve patient interactions and promote dignity in healthcare settings.